Airway inflammation, basement membrane thickening and bronchial hyperresponsiveness in asthma. Issue 4 (1st April 2002) - Ward, C; Pais, M; Bish, R; Reid, D; Feltis, B; Johns, D; Walters, E H
Abstract : Background: There are few data in asthma relating airway physiology, inflammation and remodelling and the relative effects of inhaled corticosteroid (ICS) treatment on these parameters. A study of the relationships between spirometric indices, airway inflammation, airway remodelling, and bronchial hyperreactivity (BHR) before and after treatment with high dose inhaled fluticasone propionate (FP 750 μg bd) was performed in a group of patients with relatively mild but symptomatic asthma. Methods: A double blind, randomised, placebo controlled, parallel group study of inhaled FP was performed in 35 asthmatic patients. Bronchoalveolar lavage (BAL) and airway biopsy studies were carried out at baseline and after 3 and 12 months of treatment. Twenty two normal healthy non-asthmatic subjects acted as controls. Results: BAL fluid eosinophils, mast cells, and epithelial cells were significantly higher in asthmatic patients than in controls at baseline (p<0.01). Subepithelial reticular basement membrane (rbm) thickness was variable, but overall was increased in asthmatic patients compared with controls (p<0.01). Multiple regression analysis explained 40% of the variability in BHR, 21% related to rbm thickness, 11% to BAL epithelial cells, and 8% to BAL eosinophils. The longitudinal data corroborated the cross sectional model. Forced expiratory volume in 1 second improved after 3 months of treatment with FP with no further improvement at 12 months. PD20 improved throughout the study. BAL inflammatory cells decreased following 3 months of treatment with no further improvement at 12 months (p<0.05 v placebo). Rbm thickness decreased in the FP group, but only after 12 months of treatment (mean change –1.9, 95% CI –3 to –0.7 μm; p<0.01 v baseline, p<0.05 v placebo). A third of the improvement in BHR with FP was associated with early changes in inflammation, but the more progressive and larger improvement was associated with the later improvement in airway remodelling. Conclusion: Physiology, airway inflammation and remodelling in asthma are interrelated and improve with ICS. Changes are not temporally concordant, with prolonged treatment necessary for maximal benefit in remodelling and PD20 . Determining the appropriate dose of inhaled steroids only by reference to symptoms and lung function, as specified in current international guidelines, and even against indices of inflammation may be over simplistic. The results of this study support the need for early and long term intervention with ICS, even in patients with relatively mild asthma.